Copper‐Catalyzed Aerobic Annulation of Hydrazones: Direct Access to Cinnolines. Issue 21 (18th September 2017) - Lan, Chunling; Tian, Zhuang; Liang, Xuchun; Gao, Mingchun; Liu, Wenting; An, Yu; Fu, Wencheng; Jiao, Guanming; Xiao, Junjie; Xu, Bin
Abstract: A novel method was developed for the construction of biologically active poly‐substituted cinnolines from easily accessible hydrazones in good to excellent yields. A simple copper catalyst could efficiently promote C−N bond formation through selective C−H functionalization and dehydrogenative amination. Furthermore, the inert C−Heteroatom (O/F/N) bonds are susceptible to cleavage in high selectivity in the newly developed aerobic annulation, in preference to the alternative C−H bond, which is left intact. Abstract :